2020
DOI: 10.1111/jasp.12704
|View full text |Cite
|
Sign up to set email alerts
|

Interventions stimulating prosocial helping behavior: A systematic review

Abstract: This systematic review of the literature aims to identify, analyze, and synthesize studies assessing the effectiveness of interventions stimulating prosocial behavior. It concentrates on helping behavior and covers experimental and quasi‐experimental research concerning interventions carried out in different settings. This review was performed in accordance with the PRISMA guidelines. Of the initial sample of 4,653 publications found in databases, 49 articles met our inclusion criteria and were classified as e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 79 publications
4
29
0
Order By: Relevance
“…On the other hand, the significant association between psychological flexibility and prosociality as shown in our model further indicates that prosociality is potentially malleable through ACT leading to better mental health outcomes. In fact, interventions that stimulate prosocial behaviours have been recently reviewed by Mariola and colleagues (2020), showing that psychological approaches which focus on emotional regulation, cultivation of empathy, perspective-taking, gratitude, and compassion increase the altruistically motivated prosocial behaviours of an individual [ 58 ]. As Mariola et al’s work did not find the use of ACT targeting at prosociality, implying the need for future ACT studies to examine whether addressing this malleable factor can nurture people with helping attitude and behaviour as an alternative way of coping.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the significant association between psychological flexibility and prosociality as shown in our model further indicates that prosociality is potentially malleable through ACT leading to better mental health outcomes. In fact, interventions that stimulate prosocial behaviours have been recently reviewed by Mariola and colleagues (2020), showing that psychological approaches which focus on emotional regulation, cultivation of empathy, perspective-taking, gratitude, and compassion increase the altruistically motivated prosocial behaviours of an individual [ 58 ]. As Mariola et al’s work did not find the use of ACT targeting at prosociality, implying the need for future ACT studies to examine whether addressing this malleable factor can nurture people with helping attitude and behaviour as an alternative way of coping.…”
Section: Discussionmentioning
confidence: 99%
“…The mediating role of prosociality as hypothesized in this study was only partially supported, as such relationship was only found in the Hong Kong and the Eastern Europe samples. In literature, studies have indicated that engaging in various forms of prosocial behaviors (i.e., helping for the benefits of others) would promote emotional well-being, empathy and social connectedness [ 59 , 60 , 61 ], while such positive impacts could be brought by mechanisms through influencing oxytocin release and reward circuitry system in the brain [ 61 , 62 , 63 ]. Furthermore, transcending self-interest to advance the welfare of others becomes an intrinsic motivation for adhering to public health measures against the COVID-19 spread (e.g., physical distancing measures, wearing a face mask, social isolation rules to protect others from COVID-19, more than that of protecting oneself) [ 64 ], or to get vaccinated against COVID-19 [ 65 , 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review of studies on interventions promoting prosocial helping behavior (Laguna et al, 2020c ) and a meta-analysis of interventions targeted at children and adolescents (Mesurado et al, 2019 ) demonstrated that some of these interventions were, at least moderately, effective. However, the existing research has focused mostly on children, and the interventions were typically delivered at schools and kindergartens.…”
Section: Introductionmentioning
confidence: 99%
“…Research demonstrated that it was possible, at least to some degree and for some time, to increase prosocial behavior through interventions (Mesurado et al, 2019 ; Laguna et al, 2020c ). It was therefore reasonable to expect that our intervention would also result in the enhancement of prosocial behavior, encouraging it in different situations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation